Examining student satisfaction with higher education services: using a new measurement tool - Thorsten Gruber; Stefan Fuss; Roediger Voss; Michaela Glaeser-Zikuda (2010)
Purpose – This paper aims to investigate how students perceive the services they are offered at a German university and how satisfied they are with them. Design/methodology/approach – An evaluation study using a new tool to measure 15 dimensions of student satisfaction at an institutional level that covers most aspects of student life was used. It was decided to develop a new measurement tool as many existing surveys are poorly designed, lack standardization and give no evidence concerning reliability or validity. Questionnaires were handed out in eight lectures for the pilot study and 18 lectures for the main study. The response rate was 99 percent. A total of 374 students (pilot study) and 544 students (main study) filled in the newly developed questionnaires using Likert scales. Findings – The study gave a valuable insight into how students perceive the quality of the services offered at a university and how satisfied they are with these offerings. The results show that students' satisfaction with their university is based on a relatively stable person-environment relationship. Thus, the satisfaction of students seems to reflect quite well perceived quality differences of offered services and of the wider environment. Students were particularly satisfied with the school placements and the atmosphere among students. Students were mostly dissatisfied with the university buildings and the quality of the lecture theatres. Research limitations/implications – As the study involved only two samples of students from one university, the results cannot be generalized to the German student population as a whole. Originality/value – The study was the first to successfully apply a measurement tool, which has previously not been used. The study has hopefully opened up an area of research and methodology that could provide considerable further benefits for researchers interested in this topic. It also shows how the concept of student satisfaction could be assessed in future studies.